PEMBERDAYAAN MASYARAKAT DAN OPTIMALISASI PENGGUNAAN GOOGLE CLASSROM BERBASIS E-LEARNING PADA MASA PANDEMI-COVID-19 - Qurotul Ayuni; Acep Mulyadi; Abdul Ghofur (LPPM Universitas Islam 45, 2022)
The impact of the emergence of covid in the education sector made the Minister of Education and Culture (Mendikbud) issue circular letter No. 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period of the December-19 Corona Virus Spread. In order to break the chain of spread of this virus, the government recommends closing learning in schools and implementing online learning. The method used in this Community Service is counseling and training regarding the learning process via google classroom while the result is increased knowledge about using google classroom as a supporting media for e-learning.